KAJIAN BIOFISIK AGROFORESTRI HERBAL UNGGULAN PADA BEBERAPA KETINGGIAN TEMPAT DI PEGUNUNGAN MENOREH KABUPATEN KULON PROGO D.I. YOGYAKARTA - , NANANG HERDIANA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Herbal agroforestry is interesting land management system and has been developed by people in Kulonprogo on various biophysical environment, stand structure and management of privately owned forest. The research was carried out in privately owned forest at Mountains Menoreh purposively selected based on three stratum of herbal agroforestry place, ie: lowlands (< 300 masl), middle lands (300 - 600 masl) and uplands (> 600 masl). The research was accomplished in six months through measurement of vegetation parameters, biophysical conditions, measurement of herbal plant production and interview of agroforestry management systems. Analysis of data using vegetation analysis, description and regression. Research results showed that there are 16 species in lowlands dominated by teak and mahogany, 21 species on midlle lands dominanted by mahogany and falcata and 22 species on uplands dominanted by falcata and mahogany . The dominant herbal species are turmeric (lowlands), ginger (middle lands) and cardamom (uplands). The pattern of herbal crop for ginger and turmeric are alternate row, alley cropping and random mixture, while javanese turmeric (temulawak) crop pattern are alley cropping and random mixture, cardamom crop pattern is random mixture. Herbal cultivation techniques in agroforestry systems are simple, intensive cultivation is only found in ginger and cardamom. Estimate equation of herbal plant productivity are: YGinger = 943.254 + 104.933X3 + 0.776X5 â 0.083X7 â 8,196X8